2013
DOI: 10.1186/2193-1801-2-17
|View full text |Cite
|
Sign up to set email alerts
|

PepT1 mRNA expression levels in sea bream (Sparus aurata) fed different plant protein sources

Abstract: The expression and regulation of intestinal oligopeptide transporter (PepT)-1 when vegetable sources are used as a substitute for fish meal in the diet of marine fish has not yet been explored. In the present study, as part of our ongoing work on elucidating PepT1 gene expression in relation to different dietary treatments, we have now isolated and deposited in Genbank database (accession no. GU733710) a cDNA sequence representing the PepT1 in the sea bream (Sparus aurata). The “de novo” prediction of the thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 63 publications
6
35
0
Order By: Relevance
“…The PepT2 variant, which is a low capacity/high affinity transporter (Romano et al, 2006), is highly expressed at the distal section of the intestine, where it can retain the absorption rate of small peptides at lower substrate concentrations. While PepT1 had been widely studied in fish in relation to protein utilization (Dabrowski et al, 2003; Hakim et al, 2009; Terova et al, 2013), there is little work on PepT2. In mammals PepT2 is mainly associated with the re-absorbance of peptide in the kidney (Silbernagl et al, 1987; Daniel and Kottra, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PepT2 variant, which is a low capacity/high affinity transporter (Romano et al, 2006), is highly expressed at the distal section of the intestine, where it can retain the absorption rate of small peptides at lower substrate concentrations. While PepT1 had been widely studied in fish in relation to protein utilization (Dabrowski et al, 2003; Hakim et al, 2009; Terova et al, 2013), there is little work on PepT2. In mammals PepT2 is mainly associated with the re-absorbance of peptide in the kidney (Silbernagl et al, 1987; Daniel and Kottra, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It has been found in a wide range of organisms, from bacteria to humans (Leibach and Ganapathy, 1996; Daniel et al, 2006), including many fish species (Verri et al, 2003; Sangaletti et al, 2009; Terova et al, 2013; Hart et al, 2016). PepT is a co-transporter, moving small peptides into the enterocytes.…”
Section: Introductionmentioning
confidence: 99%
“…In our study PepT1 was up-regulated in fish fed the SapH diet compared to the control and SapPhytH groups. A recent study by Terova et al (2013) described abundant expression of PepT1 in the pyloric caeca and proximal intestine whereas low expression levels were found in the stomach and in the distal intestine. The same low expression levels were found in the present study, which indicates that PepT1 is more functionally important in the proximal parts of the sea bream intestine.…”
Section: Discussionmentioning
confidence: 95%
“…Quantitative real-time PCR (qPCR) was used to analyze the mRNA expression of previously reported markers for intestinal inflammation and function, including immunoglobulin M heavy chain (IgM), cluster of differentiation 8 (CD8), T-cell receptor beta (TCR␤), Interleukin 1␤ (IL1␤), transforming growth factor ␤ (TGF␤), major histocompatibility complex I (MHC-I), major histocompatibility complex II (MHC-II), tumor necrosis factor ␣ (TNF␣), caspase 3 (Casp3), proliferating cell nuclear antigen (PCNA), fatty acid binding protein (intestinal; FABP2), intestinal peptide transporter (PepT1) and Aquaporin 8 (Aqp8) (Krogdahl et al, 2000;Skugor et al, 2011;Kortner et al, 2012;Marjara et al, 2012;Terova et al, 2013;Venold et al, 2013). Previously validated and published gene-specific primers (Table 2) were used to quantify TCR␤, MHC-II (Cerezuela et al, 2012), IgM (Estensoro et al, 2012), IL1␤ ), FABP2 (Calduch-Giner et al, 2012, for the remaining genes primers were designed using Primer3 software (http://frodo.wi.mit.edu/primer3).…”
Section: Gene Expressionmentioning
confidence: 99%
“…PepT1 is a member of the proton oligopeptide cotransporter family, transporting all potential 400 dipeptides and 8,000 tripeptides (Daniel & Kottra, ). Previous studies reported that PepT1 was highly expressed in fish small intestine from proximal to distal regions, which suggested that the whole intestine may be involved in peptide absorption (Rønnestad et al, ; Terova et al, ; Xu et al, ). In our study, the expression of PepT1 had been analysed in different intestinal segments.…”
Section: Discussionmentioning
confidence: 98%